Additive manufacturing of SiOC scaffolds with tunable structure-performance relationship. Issue 15 (December 2021) - Huang, Kai; Elsayed, Hamada; Franchin, Giorgia; Colombo, Paolo
Abstract: Aiming at optimizing the performance of porous ceramics through structural optimization, this work explored the properties variation achieved by designing different patterns in SiOC log-pile structures fabricated by direct ink writing. Specifically, we investigated the effect of filament diameter, spacing between filaments and angle of deflection between adjacent layers on the compression strength and gas permeability of these structures. Results confirm that mechanical performance could be tuned by designing the structures' architectural features, such as the spacing between filaments and the angle of deflection between layers, leading to changes in the contact area of filaments belonging to adjacent layers. Permeability decreased with varying angle of deflection from 90 ° to 15 °, due to the higher tortuosity of the flow paths. This enables to optimize the strength and permeability of the structure without reducing the porosity of the component.